Can Guided Play and Storybook Reading Promote Children's Drawing Development?. (January 2019) - Sawyer, Jeremy E.; Goldstein, Thalia
Children's drawings are implicated in their emotional, cognitive, artistic, and semiotic development, raising the question of how early educators may best facilitate drawing development. This study compared three activities to determine their relative efficacy in promoting children's drawing. Seventy-seven preschoolers from a Head Start program were randomly assigned to one of three conditions: storybook reading, block building, or dramatic pretend play games (DPPG). Interventions were conducted over 8 weeks, and children's free drawings during each session were rated on five dimensions: creativity, talent, spatial complexity, color, and human content. Taken together, the interventions produced significant growth in overall drawing, particularly for children who were initially more skilled at drawing. Comparisons indicated that storybook reading and block building generated significantly better overall drawing than DPPG. Story time was more beneficial than DPPG for creativity, talent, and spatial complexity, while block building was more beneficial than DPPG for children's use of color.